Practices and Behaviors Regarding the Use of Analgesics - Salwa Muftah Eljamay; Emhamed Boras; Maha Saad Almzaini; Mabrouka Munsif Jebreil (CV. Literasi Indonesia, 2023)
Analgesic medicines are the most regularly prescribed pharmaceuticals globally. The goal of this project is to learn about and improve analgesic use practices through an education campaign. Materials and Procedures: This cross-sectional, online survey was conducted for 340 respondents in Derna City Libya region between 15 April 2022 and two November 2022. Result: Males were 49 (14.4%) and females were 291 (85.6%), the Mean & S.D (1.86, 0.352), ages 10 - 65 years old, the Mean & S.D (1.86, 0.352), (3.92, 2.082). The greatest percentage of excellent at the economic level is 153 (45.0%). The lowest score for superb is 6 (1.8%), followed by 45% for a decent scenario, 35% for a not-so-poor situation, and 7.1% for a horrible one. The percentage of university graduates is 203 (59.7%), whereas the percentage of illiterate people is 3 (0.9%). The P-Value of understanding the adverse effects of using analgesics regularly (0.000 0.05), the correlation is significant for there is a link between knowledge and educational level, the relationship between knowledge and educational level demonstrates that a p-value greater than 0.05 indicates that there is no relationship between knowledge and educational level. Conclusion: No matter how high a person's education level is, it does not substitute for understanding the usage of analgesic drugs and there's no correlation between a scientific degree and citizens' understanding of the hazards of utilizing analgesic drugs without a prescription.